2012 15th Euromicro Conference on Digital System Design 2012
DOI: 10.1109/dsd.2012.111
|View full text |Cite
|
Sign up to set email alerts
|

reMORPH: A Runtime Reconfigurable Architecture

Abstract: Programmable hardware built on a regular architecture can partially alleviate the problem of increased defect densities associated with transistor scaling by dynamically wiring around the defects [1]. The fine granularity of FPGAs is however unsuitable for effectively exploiting runtime reconfiguration because of the high overheads involved. A coarse grain reconfigurable array with malleable communication links -reMORPH -is proposed in this paper. The compute tile uses DSP48E and BRAM embedded blocks in a Xili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…An alternative solution is to build arrays of customized TM FUs and interconnect on the FPGA, similar to CGRAs [17]. A number of different interconnect styles for connecting between FUs can be used, with the most common being: island style [6], [8], nearest neighbor [20], [16] and to a lesser extent linear interconnect [3], [9]. The overhead of the interconnect network, particularly for island style and nearest neighbor interconnects, contribute to a significant FPGA resource utilization.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative solution is to build arrays of customized TM FUs and interconnect on the FPGA, similar to CGRAs [17]. A number of different interconnect styles for connecting between FUs can be used, with the most common being: island style [6], [8], nearest neighbor [20], [16] and to a lesser extent linear interconnect [3], [9]. The overhead of the interconnect network, particularly for island style and nearest neighbor interconnects, contribute to a significant FPGA resource utilization.…”
Section: Related Workmentioning
confidence: 99%
“…The reMORPH overlay [20] better targets the FPGA fabric, with an FU consuming 1 DSP Block, 3 block RAMs, 196 LUTs and 41 registers. To reduce overhead, the reMORPH FU does not use decoders resulting in a 72-bit instruction memory (supporting up to 512 instructions) which also over utilizes the BRAMs.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Paul et al have reported that if the reconfiguration is limited to changing the connectivity at runtime, the overheads are typically very low [1]. This allows fairly large circuits to be implemented modularly in a time multiplexed manner which makes the implementation area and power efficient.…”
Section: D-fft Architecturementioning
confidence: 99%
“…reMORPH [1] is a reconfigurable nearest neighbor mesh connected array of coarse grain reconfigurable tiles as illustrated in Figure 2. Modern FPGAs have hard DSP macros and lots of embedded memory which have been used to design the processing element (PE) to operate at 400 MHz with a very low footprint of 200 slice LUTs.…”
Section: D-fft Architecturementioning
confidence: 99%